2002
DOI: 10.1177/0741713602052003005
|View full text |Cite
|
Sign up to set email alerts
|

Know Thyself: The Impact of Portfolio Development on Adult Learning

Abstract: Thousands of years ago the Greeks carved above their temples the phrase “know thyself,” two simple words that imply a lifetime of investigation. Throughout the ages philosophers and scholars have emphasized the importance of self-knowledge as an outcome of learning. One teaching strategy that facilitates self-knowledge among adult students is the creation of an experiential learning portfolio. This study describes and explains how the development of such a portfolio affected a diverse group of adult undergradu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
69
0
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 16 publications
2
69
0
3
Order By: Relevance
“…Herring, Hibbs, Morgan, and Notar (2007) describe how student success and motivation for learning increase through the use of standards-based digital portfolios. Brown's (2002) findings suggest that the development of a portfolio increases students' understanding of "what, why, and how they learned" (p. 228), enhances their communication and organization skills, and reinforces the importance of reflection in learning. In my course, I introduce the learning portfolio assignment with the following definition (Cassidy, 2008): Your personal version of the course, documenting your learning throughout the term (and briefly, what you will take away with you), and presented in creative, varied, and multi-linked ways that include tangible evidence, examples, connections and reflections, based on three key criteria.…”
Section: What Is a Learning Portfolio?mentioning
confidence: 78%
See 1 more Smart Citation
“…Herring, Hibbs, Morgan, and Notar (2007) describe how student success and motivation for learning increase through the use of standards-based digital portfolios. Brown's (2002) findings suggest that the development of a portfolio increases students' understanding of "what, why, and how they learned" (p. 228), enhances their communication and organization skills, and reinforces the importance of reflection in learning. In my course, I introduce the learning portfolio assignment with the following definition (Cassidy, 2008): Your personal version of the course, documenting your learning throughout the term (and briefly, what you will take away with you), and presented in creative, varied, and multi-linked ways that include tangible evidence, examples, connections and reflections, based on three key criteria.…”
Section: What Is a Learning Portfolio?mentioning
confidence: 78%
“…Learning portfolios can appear in hard copy or electronically. Some related terms include course portfolios (e.g., University of Nebraska Lincoln, 2009), professional portfolios (Bossers, Kernaghan, Hodgins, O'Connor, & Van Kessel, 1999), and experiential learning portfolios (Brown, 2002), all of which have been used, across disciplines, in a variety of contexts including K-12, post-secondary, and professional programs.…”
Section: What Is a Learning Portfolio?mentioning
confidence: 99%
“…All course content is on the web, all student interactions with tutors, the institution, and each other including assessment is dealt with electronically While there have been many initiatives aimed at supporting women returners (Shaw, 1999), these have generally been face to face or built around printed materials. Traditionally, 'return to work' courses, and adult education courses, help participants build portfolios, but these are usually hard copy collections (Brown 2002, Baume 2003. We decided to adopt an ePortfolio on this course because of the elearning approach used throughout the course and because we had an available prototype ePortfolio software package (Profile).…”
Section: Background: Women Returnersmentioning
confidence: 99%
“…Of more interest here is the evidence provided by recent research about other types of contributions made by portfolio construction, contributions that deal with broader issues of learning and knowing. For example, using interviews with adult learners who had developed experiential learning portfolios, Brown (2002) identified the following benefits of portfolio construction: "(a) marked increase in the participants' self knowledge after portfolio development; (b) a greater recognition of the value of learning from work and from mentors; and (c) improved communication and organization skills and greater appreciation of the role of reflection in recognizing learning" (p. 234). Klenowski (2000) discovered through surveys and interviews that portfolio development helped preservice teachers integrate their learning, understand applications of their knowledge to teaching, and develop confidence as teachers and learners.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of who experiences learning benefits, Brown (2002), after profiling dimensions of learning, observed that "not everyone experiences the same degree of learning" (p. 241). Cambridge (2008) also highlighted the issue of who learns with his finding that only 18 percent of active users of a Minnesota-based portfolio tool reported a substantial amount of learning as a result of their activity-a finding that raises questions about the amount of learning experienced by other participants.…”
Section: Introductionmentioning
confidence: 99%